From the lab to the open field: The use of adaptation and socialization protocols with rattus norvegicus (2011)
The goal of this paper is to introduce an adaptation-and-socialization protocol for animal subjects Rattus norvegicus, Wistar strain, into a research project that aims to train these animals to detect explosives, both in laboratory and open field. We describe the design of the home cages, which are different from the vivarium's standard home cages. Next, the exposure of the animals to different physical environments is related. Finally, the inter-specific socialization protocol of the rats with humans and other animals is described.